PARTISIPASI MASYARAKAT SEBAGAI STRATEGI MEWUJUDKAN GOOD GOVERNANCE DALAM MENINGKATKAN PEMBANGUNAN INFRASTRUKTUR PENDIDIKAN: (Studi Kasus: Desa Cipinang, Kecamatan Rumpin, Kabupaten Bogor) - Ayu Kholilah (Jurnal Wahana Bina Pemerintahan, 2023)
This study is focused on knowing and understanding the phenomenon that occurs regarding participation of public society as a strategy to realize good governance in improving the development of educational infrastructure and what is the factors that affect the level of public society’s participation. According to the research focus, this type of research is descriptive qualitative, which provides a real description of public society’s participation. The data presented in this study are primary and secondary data, which were collected by means of observation, interviews and documentation studies. The data analysis technique of this research uses the Miles and Huberman technique, it is from data collection, data reduction or data processing, verification and then data presentation. The results of research and discussion, it is known that in improving the development of educational infrastructure in Cipinang Village, Rumpin District, Bogor Regency, there are still people who are not aware of the importance of participation. Community participation is carried out in 4 (four) forms from the stages of decision making, implementation of activities, monitoring and evaluation, and utilization of development results. In its implementation there are inhibiting factors, namely the lack of socialization, cultural factors and economic factors. While the supporting factors are the availability of discussion forums and opportunities provided by the Village Government to the community. As for the things that are suggested, such as the Village Government should further improve socialization, interact with the community and conduct development activities in economic.